Manajemen Keuangan Rumah Tangga Menuju Mandiri Pangan: Pelajaran Berharga Dari Petani Udang Vaname Desa Mootinelo Kabupaten Gorontalo Utara - Arfan Nusi; Melani Musran; Wahyu Dian; Anisa Tute; Setyo Panigoro; Nurfitriyani Amelia; Muhammad Basir; Lolanda Idrus; Basid Abd.Azis; Arman Ma'ruf (JIEF : Journal of Islamic Economics and Finance, 2021)
This research aims to examine the household financial management of people who work as Vannamei Shrimp Farmers in building food independent in Mootinelo, North Gorontalo District. Using a qualitative research method with a descriptive study approach and the techniques of collecting data used are interviews, observations, and documentation. This research shows that the household financial management in Mootinelo, North Gorontalo district is divided into two. First, there are households that experience financial difficulties after being hit by bad weather that makes vanname shrimp stunted, then by the covid-19 pandemic. Second, there are households that are able to manage finances well even the conditions are not well. This second household is said to be at the food independent level